Periodontal Disease Risk Factors Assessment in Association with Frequency of Tooth Brushing - Noor-ul-Ain Qazi, Amna Bilal, Fatima Siraj, Shahwar Siddiq, Hafsa Gul, Madiha Riasat, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To analyze the co-relation between frequencies of tooth brushing as a periodontal risk assessment tool in a population. Study design: Cross Sectional Survey Place and duration of study: Bacha Khan Medical College, Mardan from 1st January 2021 to 31st December 2021. Methodology: Four hundred and eleven participants were enrolled. Data was collected by administering the study questionnaire including 14 items assessing risk factors for periodontal disease as well as their oral hygiene habits. Descriptive statistics were used for data summarization and presentation. Results: Approximately 34.3% of study participants claimed to brush twice daily and 61.6% once daily. Mean age was 22.1 years and majority of them females constituting 66.7%. 39.33% had a history of bleeding gums while 28.2% had swollen gums. 51% of the subjects reported brushing for less than 2 minutes duration. 67% participants of population were of upper middle socioeconomic status. Conclusion: The clear correlation establish amongst risk of emerging periodontal disease and occurrence of tooth brushing. Keywords: Periodontal disease, Oral hygiene, Risk factors, Tooth brushing